Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s00436-018-5869-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary antioxidant supplementation in a vertebrate host on the infection dynamics and transmission of avian malaria to the vector

Abstract: Host susceptibility to parasites is likely to be influenced by intrinsic factors, such as host oxidative status determined by the balance between pro-oxidant production and antioxidant defences. As a result, host oxidative status acts as an environmental factor for parasites and may constrain parasite development. We evaluated the role of host oxidative status on infection dynamics of an avian malarial parasite by providing canaries (Serinus canaria) with an antioxidant supplementation composed of vitamin E (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
0
5
0
1
Order By: Relevance
“…Results demonstrated that treatment with GSH accelerates the evolution of the disease in PbA-infected mice as well as the liver damage, while the treatment with vitamin C controls the disease outcome and mitigates the hepatotoxicity associated with the condition. It is widely described in literature that human malaria is characterized by intense hepatotoxicity and liver dysfunction, and although hepatic dysfunction in malaria is not fully understood, oxidative stress is often related to this condition [17]. As demonstrated in both human patients and animals models, liver damage during Plasmodium infection occurs as a result of free heme accumulation that triggers severe oxidative stress and stimulates proinflammatory response by tumor necrosis factor (TNF-α) release [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results demonstrated that treatment with GSH accelerates the evolution of the disease in PbA-infected mice as well as the liver damage, while the treatment with vitamin C controls the disease outcome and mitigates the hepatotoxicity associated with the condition. It is widely described in literature that human malaria is characterized by intense hepatotoxicity and liver dysfunction, and although hepatic dysfunction in malaria is not fully understood, oxidative stress is often related to this condition [17]. As demonstrated in both human patients and animals models, liver damage during Plasmodium infection occurs as a result of free heme accumulation that triggers severe oxidative stress and stimulates proinflammatory response by tumor necrosis factor (TNF-α) release [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrate that liver injuries caused by Plasmodium infection are associated with unbalance of the antioxidant system in hepatocytes [ 17 ]. However, it remains unclear if treatment with antioxidants is able to protect the liver of infected subjects.…”
Section: Introductionmentioning
confidence: 99%
“…An insecticide comprising straight-chain octanoic, nonanoic, and decanoic saturated fatty acids (C8, C9, and C10) called C8910, displayed insecticidal effects on different strains of Anopheles funestus [ 152 ]. Supplemented birds with olive oil and vitamin E increased the transmission to the vector, indicating that vertebrate host oxidative status influences parasite transmission to the vector [ 153 ].…”
Section: Fatty Acids and Malariamentioning
confidence: 99%
“…1). Varios estudios han relacionado la presencia de hemosporidios con niveles bajos de hematocrito (Booth y Elliott 2002;Delhaye et al 2018), pudiendo ser consecuencia de una anemia hemolítica severa (Desser y Bennett 1993;Palinauskas et al 2011).…”
Section: Variables Hematológicas Eritrocitosunclassified